Global analysis reveals persistent shortfalls and regional differences in availability of foods needed for health - Costlow, Leah; Herforth, Anna; Sulser, Timothy B.; Cenacchi, Nicola; Masters, William A. (Elsevier, 2025)
Sufficient food is available in the world for all people to consume sufficient calories, but not healthy diets. This study traces historical and projected changes in global food systems toward alignment with the new Healthy Diet Basket (HDB) used by UN agencies and the World Bank to monitor the cost and affordability of healthy diets worldwide. Using the HDB as a standard to measure adequacy of national, regional and global supply-demand balances, we find substantial but inconsistent progress toward closer alignment with dietary guidelines, with large global shortfalls in fruits, vegetables, and legumes, nuts, and seeds, and large disparities among regions in use of animal source foods. Projections show that additional investments aimed at reducing chronic hunger would modestly accelerate improvements in adequacy where shortfalls are greatest, revealing the need for complementary investments to increase access to under-consumed food groups especially in low-income countries.